Das Deutsch der Migranten - Deppermann, Arnulf (Jahrbuch des Instituts für Deutsche Sprache, 2013)
The subject of this annual volume for 2012 is the usage and forms of German as spoken by immigrants. The work addresses the acquisition of German as a second language, particularities in the German spoken by individuals with an immigrant background, the role of language for the transformation of self-identity, as well as communication between immigrants and German natives.